The relationship between sarcopenia and mortality in Chinese community-dwelling adults: a 7-year cohort study with propensity score matching and Mendelian randomization - Xiong, Lijiao; Liao, Tingfeng; Guo, Tianting; Zeng, Zhaohao; Wang, Shuojia; Yang, Guangyan; Wang, Xiaohao; Wang, Xinyu; Zhu, Jing; Zhao, Pengfei; Li, Yanchun; Li, Lixing; et al. (Frontiers in Endocrinology, 2023)
Background: Background: Sarcopenia has been linked to adverse health outcomes, including an increased risk of mortality. This study aimed to assess the 7-year mortality risk of sarcopenia in a community-based population in China and explore the causal relationship between components of sarcopenia and any death. Methods: Data were sourced from the China Health and Retirement Longitudinal Study (CHARLS), conducted between 2011 and 2018. Sarcopenia was diagnosed using the Asian Working Group for Sarcopenia (AWGS) 2019 criteria. Logistic regression, Kaplan-Meier survival analysis, propensity score matching with inverse probability of treatment weighting. Mendelian randomization (MR) analyses, conducted using European population data, were utilized to assess causality between sarcopenia and any death.Results: The study included 9,006 participants, 3,892 had no sarcopenia, 3,570 had possible sarcopenia, 1,125 had sarcopenia, and 419 had severe sarcopenia. Over 7 years of follow-up, there were 871 deaths, including 196 with sarcopenia, and 133 with severe sarcopenia. The KM curves showed that sarcopenia had a higher risk of mortality.Compared to no sarcopenia, the odds ratios (ORs) of sarcopenia for 7-year mortality were 1.41 (95% CI 1.06-1.87) after adjusting for confounding variables (P<0.05). The ORs of severe sarcopenia were 2.11 (95% CI 1.51-2.95). Propensity score-matched analysis and inverse probability of treatment weighting analysis confirmed these findings. The adjust ORs for sarcopenia and 7-year mortality were 2.94 (95% CI, 1.6-5.39) in the 45-60 age group, 1.72 (95% CI, 1.11-2.68) in the 60-80 age group, and 3 5.03 (95% CI, 0.48-52.65) in the ≥80 age group. The ORs for severe sarcopenia and 7year mortality were 6.92 (95% CI, 1.95-24.5) in the 45-60 age group, 2.59 (95% CI, 1.61-4.17) in the 60-80 age group, and 12.52 (95% CI, 1.18-133.18) in the ≥80 age group. The MR analyses, leveraging the inverse variance weighted (IVW) method, unveiled substantial causal links between low hand grip strength in individuals aged 60 and older, the usual walking pace, and mortality risk.Conclusion: This study underscores the significant impact of sarcopenia and its components on mortality risk within the Chinese population. Particularly, low hand grip strength and usual walking pace emerge as noteworthy contributors to mortality risk.